A new method of accurate broken rotor bar diagnosis based on modulation signal bispectrum analysis of motor current signals. (January 2015) - Gu, F.; Wang, T.; Alwodai, A.; Tian, X.; Shao, Y.; Ball, A.D.
Abstract: Motor current signature analysis (MCSA) has been an effective way of monitoring electrical machines for many years. However, inadequate accuracy in diagnosing incipient broken rotor bars (BRB) has motivated many studies into improving this method. In this paper a modulation signal bispectrum (MSB) analysis is applied to motor currents from different broken bar cases and a new MSB based sideband estimator (MSB-SE) and sideband amplitude estimator are introduced for obtaining the amplitude at ( 1 ± 2 s ) f s ( s is the rotor slip and f s is the fundamental supply frequency) with high accuracy. As the MSB-SE has a good performance of noise suppression, the new estimator produces more accurate results in predicting the number of BRB, compared with conventional power spectrum analysis. Moreover, the paper has also developed an improved model for motor current signals under rotor fault conditions and an effective method to decouple the BRB current which interferes with that of speed oscillations associated with BRB. These provide theoretical supports for the new estimators and clarify the issues in using conventional bispectrum analysis. Highlights: An electrical current signal model is derived to include the effect of phases. An effective method is investigated to demodulate small modulation signals. Modulation signal bispectrum is proposed to separate and estimate sidebands. A new formula is proposed for estimating the number of broken rotor bars.